Gospel Poetry as Evangelism in Contemporary Contexts in Zimbabwe: The Case of Spoken Word Tribe. - Cletus Moyo (Pharos Journal of Theology, 2018)
The Christian faith is an ideal ground for the arts to grow in, irrespective of typology. God can only be known metaphorically speaking and the Holy Scriptures are clear about this aspect. Consequently, the Holy Bible is full of metaphors which are in poetic form poems. Poetry that is religiously oriented enthuses an audience about religious knowledge and even practices, and mostly elevate human understanding on what constitutes a spiritual life. Spoken Word Tribe (SWT), a group of young Christians desiring to put their poetic talent in the advancement of the Gospel of Jesus Christ, has recently been in the forefront of Gospel poetry in Bulawayo, a phenomenon that is worthy of research. These young Christians deploy poetic skills to the service of the Gospel and seek to remain ‘creative/ artistic’ and at the same time ‘sound’ in reaching out to people with the Gospel of Jesus Christ especially the young people in urban contexts. This paper examines the phenomenon of using poetry to advance the Gospel of Jesus Christ. It uses the case study of "Spoken Word Tribe", a group of young people in Bulawayo in Zimbabwe who are deploying their poetic skills in the service of the Gospel. The group is doing poetry as a way of advancing the Gospel of Jesus Christ both within and outside Church settings. The researcher argues that this kind of approach is at the intersection of Art and the Gospel resulting in art being in service of the Gospel, a means to an end rather than an end in itself. This, the researcher observes, has a potential of making young Christians reach out to more of their peers with the Gospel in a way that is relevant to their contexts. It is a demonstration of adapting ministry strategies without changing the unchanging message of the Gospel. The researcher also observes that there are however some sections of Christians that see such an approach to the Gospel as too relaxed and thus begrudge it.